MARKETING STRATEGY DESIGN FOR CAGAK CIANJUR PRIMARY CLINIC TO INCREASE CAPITATION AND NON-CAPITATION REVENUE FROM BPJS-HEALTH - Berutu, Kristiyanto; Lahindah, Laura (Ridwan Institute, 2024)
This study aims to analyze the internal and external conditions that affect the performance of Pratama Cagak Clinic and formulate effective marketing strategies to increase revenue from capitation and non-capitation services. This study adopts a qualitative method with a case study approach to delve into the factors that affect marketing in the clinic, including BPJS policies and local patient preferences. The results of this analysis are then mapped in SWOT and used to compile the TOWS Matrix and Quantitative Strategic Planning (QSPM) to prioritize strategies that can increase revenue and operational sustainability of clinic operations. The five force model approach is used to understand the factors affecting the health industry in Cianjur Regency, namely, the PESTEL and Porter's Five Forces frameworks. The objective of this study is to provide a comprehensive overview of the condition of the clinic based on external and internal analysis, as well as interviews with several heads of health centers and managers of the primary clinic. In addition, a structured strategy and focusing on continuous evaluation are implemented to increase general patient visits and the number of pregnant women participating in the BMJ-Kesehatan capitation scheme.